PERANCANGAN RANGKAIAN APLIKASI DASAR TRANSISTOR - Rahmad, M; Angelia, Yessy; Sahal, Muhammad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
Â This research purpose to design an instrument capable to run directly bipolar transistors function as an amplifier in current, AC voltage, and as switching. This type of research is research and development, which is developing a basic application instrument for bipolar transistors. The testing to bipolar transistor elementary application instrument use measuring instrument of microampere meter, voltmeter, a generator function, and digital oscilloscope. The reached result indicates that this instrument can prove to gain the current and gain voltage of the transistor. That thing is seen from existence mean gain current 119,99 - 480. While voltage gain 1,46 - 5,29. Transistor application for switching found the fact that transistor starts to have as switching at the voltage base-emitter 0,58 - 0,7 Volt, the result is equal to a bipolar transistor barrier voltage to emission a current from pin emitter to pin collector.Â